SEJARAH PERKEMBANGAN KETHOPRAK SISWO BUDOYO - Endang Waryanti (JURNAL IKADBUDI, 2015)
This article describe about history of traditional theatre art. This call Kethoprak Siswo Budoyo. The theatre group of Kethoprak Siswo Budoyo lead by Ki Siswondo who has high acting talent. He is very popular in Javanesse community that like show theatre. Kethoprak Siswo Budoyo always give morality, spirituality and  sociaty value to audience. Therefore kethoprak Siswo Budoyo have some fanatic fans. Everyone like Kethoprak Siswo Budoyo because this theatre group teach character education.Keyword : history, kethoprak, character education